2013
DOI: 10.1103/physreve.87.042302
|View full text |Cite
|
Sign up to set email alerts
|

Thermal conductivity of supercooled water

Abstract: The heat capacity of supercooled water, measured down to −37 ℃, shows an anomalous increase as temperature decreases. The thermal diffusivity, i. e., the ratio of the thermal conductivity and the heat capacity per unit volume, shows a decrease. These anomalies may be associated with a hypothesized liquid-liquid critical point in supercooled water below the line of homogeneous nucleation. However, while the thermal conductivity is known to diverge at the vapor-liquid critical point due to critical density fluct… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 49 publications
0
29
0
Order By: Relevance
“…Computer simulations for the TIP5P water model, reported by Kumar and Stanley,15 indicated that the thermal conductivity of supercooled water displays a minimum as a function of temperature, in marked contrast to the fluctuationinduced enhancement of the thermal conductivity in the vicinity of the vapor-liquid critical point of water. 16 In a previous paper, 17 some of us showed that dynamical fluctuation effects are suppressed by the large viscosity of supercooled water. Instead it was suggested that the anomalous behavior of the thermal conductivity λ of supercooled water is of thermodynamic origin, possibly through the Bridgman equation,…”
mentioning
confidence: 99%
“…Computer simulations for the TIP5P water model, reported by Kumar and Stanley,15 indicated that the thermal conductivity of supercooled water displays a minimum as a function of temperature, in marked contrast to the fluctuationinduced enhancement of the thermal conductivity in the vicinity of the vapor-liquid critical point of water. 16 In a previous paper, 17 some of us showed that dynamical fluctuation effects are suppressed by the large viscosity of supercooled water. Instead it was suggested that the anomalous behavior of the thermal conductivity λ of supercooled water is of thermodynamic origin, possibly through the Bridgman equation,…”
mentioning
confidence: 99%
“…Furthermore, it significantly changes thermal transport properties of air-liquid interface by evaporation cooling [16]. However, quantitative analysis of temporal evolution of spreading diameter, illustrated in Figure 3, shows that the effect of incoming cold air flow has an insignificant effect on wetting dynamics on hydrophilic and hydrophobic surfaces which arise from strong crystallization process at solid-liquid interface combined with sever increase in contact line viscosity up to 8 and 4.3 fold at −30 °C and −20 °C , respectively [41,42]. Furthermore, the effect of the capillary ridge become important where exposed air flow on thin film of super cooled water comes into contact with solid material [46].…”
Section: Resultsmentioning
confidence: 99%
“…The change in the maximum spreading diameter is due to an increase of droplet internal bulk viscosity up to 8-fold [41,42]. It was shown that an increase in viscous dissipation results in a decrease in the maximum spreading diameter, as can be inferred from droplet viscous dissipation [43] where U and L are droplet impact velocity and near wall boundary layer thicknesses [44].…”
Section: Resultsmentioning
confidence: 99%
“…Example values of some of the key parameters in the model, taken from a high-seed aerodynamic flow in which the free-stream temperature is lower than but close to the freezing temperature. The data for supercooled water is taken from Hare & Sorensen (1987), Holten et al (2012), Biddle et al (2013), Hrubý et al (2014) and Dehaoui et al (2015).…”
Section: Applicability Of the Modelmentioning
confidence: 99%